The Role of Omnichannel and Service Quality to Get the Best Customer Experience for Increasing Sales in The Retail Industry - Suriansha, Reza (The Es Economics and Entrepreneurship, 2024)
The rapid development of technologies finally effects revolutionary to our daily activities especially in retail industry. This research was conducted to determine the effect of covid19 and the development of digital technology on customer behavior and how to shop. In this study there are four variables, namely Omnichannel (X1), Service Quality (X2), Customer Experience (Y1) and Sales Level (Y2). The population in this study were consumers who had bought in the retail industry with a sample of 150 respondents selected using purposive sampling method. Collecting data in this study by giving questionnaires to respondents. While in terms of data analysis, this study uses the path analysis method with the help of SPSS version 26 and smart-PLS. The results showed that: 1) OmniChannel has a positive and significant effect on Customer Experience, 2) Service Quality has a positive and significant effect on Customer Experience, 3) OmniChannel has a positive and significant effect on sales levels, 4) Service Quality has a positive and significant effect on sales levels, 5) Customer Experience has a positive and significant effect on Sales Level, 6) OmniChannel has a positive and significant effect on Sales Level through Customer Experience, 7) Service Quality has a positive and significant effect on Sales Level through Customer Experience. From this research, it is hoped that we can see how companies can increase their sales by maximizing customer experience through the use of Omnichannel strategies and service quality.